IDENTIFICATION AND COMPOTITION OF FISH TYPES IN THE WATERS OF MEUREBO RIVER, WEST ACEH - Marlian, Neneng Marlian; Mauliza, Mira; Isbah, Faliqul (Universitas Teuku Umar, 2024)
Research on the Identification and Composition of Fish Types in The Waters of Meurebo River, West Aceh, was carried out in September 2024 in the Meurebo River, West Aceh. This research aimed to determine the identification of fish types, and the composition of fish found in Sunagai Meurebo. The method used in this research was the survey method. The research locations were divided into 3, namely station 1 which was located upstream of the river, station 2 which was in the middle of the river and station 3 which was located downstream of the river. Samples were analyzed in the the Environmental Productivity (EP) Laboratory to determine morphological and morphological characteristics. Fish identification refered to books according to Saanin (1968) and Kottelat et al., (1993). The results of the research showed that 10 species had been found belonging to 5 orders, 10 families and 10 genera with 4 types of freshwater fish and 6 types of seawater fish. Based on the composition of fish species, the species Ambassis vachellii from the order Perciformes was obtained, which had the highest composition of all fish species found in the waters of the Meurebo River, namely 54% and the lowest composition was found in the species Caranx latus (1.1%), Leiognathus equulus (1 .1%) which both came from the order Perciformes, as well as the species Tor tambra (1.1%) from the order Cypriniformes.